Factors Influencing Young People's Preferences for Sharia Mortgage Financing in Indonesia - Al Fauzi, Muhammad Fuad (Indonesian Journal Publisher, 2024)
A house is a primary need for humans, this is because a house is a place to live and a place of shelter. With the increasing population, of course, the need for houses also increases, so it will affect the price. The problem of price is a problem for young people in buying a house and KPR is a solution offered so that young people can buy a house. This study aims to examine what factors influence young people's preferences for Sharia KPR. This study uses multiple linear regression analysis with SPSS 25.0 tools, and this study uses a sample size of 184 respondents. The data in this study are primary data obtained from respondents by distributing them via google form. The results of this study indicate that the variables of religiosity, Islamic branding and Islamic financial knowledge have a positive and significant effect on young people's preferences regarding Sharia KPR. The conclusion of this study states that religiosity, Islamic branding and Islamic financial knowledge have an influence on young people's preferences regarding Sharia KPR.